The Relationship Between Business Environment and Single Champion Enterprise Entrepreneurship - Wu, Chanti; Lin, Jinjin (Frontiers in Psychology, 2022)
What kind of business environment produces high single champion enterprise entrepreneurship is a new problem to be solved in entrepreneurship research. This Paper analyzes the relationship between business environment and single champion enterprise entrepreneurship from the perspective of configuration with fcQCA method based on institutional configuration theory. This Paper studies the role of business environment in promoting high single champion enterprise entrepreneurship among 80 case cities all over the country and discusses three kinds of business environment configurations of high single champion enterprise entrepreneurship and two configurations of non-high single champion enterprise entrepreneurship. There are three kinds of typical business environment element configurations which can promote high single champion enterprise entrepreneurship, namely market innovation type led by multiple resources, financial-service-driven type assisted by resources and market-driven type led by financial services, which reflect the significance of financial services and market environment.